The Effectiveness of Supervisory and Capacity-Building Measures for Temporary Land Deed Officials (PPATS) in the Preparation of Land Deeds in Aceh Besar Regency, Aceh Province - Muhammad Zulkarnaen; Mazwar; Teuku Muttaqin Mansur (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the effectiveness of legal capacity-building for Temporary Land Deed Officials (PPATS) in the preparation of land deeds in Aceh Besar Regency, Aceh Province. The research employs an empirical juridical method with a qualitative approach, utilizing data collection techniques including interviews, observation, and document analysis. This approach enables a comprehensive examination of both the normative framework and its practical implementation in the field. The findings indicate that the effectiveness of capacity-building for PPATS remains suboptimal, as the existing programs are largely administrative, incidental, and insufficient in addressing substantive legal aspects. Several factors influence this condition, including the non-legal educational background of PPATS, prevailing community legal culture, limitations in training programs, weak institutional coordination, and social pressures encountered in the practice of land deed preparation. These challenges contribute to a low level of material competence and legal prudence among PPATS in carrying out their duties. Accordingly, there is a need for a more sustainable, contextual, and competency-based capacity-building model to enhance the professionalism of PPATS. Such an approach is essential to strengthen their substantive legal understanding, improve the quality of land deeds, and ultimately support the realization of legal certainty in land administration services.